Employee Voice Behavior: Pengaruh Self-efficacy, Kepribadian Proaktif dan Work Engagement dalam Organisasi Pendidikan - Anjelica Reisa; Niko Sudibjo (Universitas Kristen Satya Wacana, 2020)
Voice behavior is the attitude that consider the goal of the organization with the willingness to give the positive input and opinion to the organization. There are so many factors that can affect Employee Voice Behavior. The purpose of this research was to examine the effect of self-efficacy, proactive personality, and work engagement on EVB. This research was done on 35 respondents among lecturers in conservatory of music UPH by analyzing the path coefficient on Smart PLS. The result showed that self-efficacy, proactive personality as endogen variable has the positive effect on EVB, meanwhile work engagement as mediator has no effect on EVB lecturers in Conservatory of Music UPH.